Theory of two-phase flow of fluid with rigid ellipsoidal particles - Diep, Nguyen Van; Phan, Nguyen Hong (Vietnam Journal of Mechanics, 1993)
In the paper [1] the general continuum theory has been developed for two phase of fluid with deformable particles of arbitrary form, where the micro deformation of the particles and the relative motion between phases are taken into account. The extended theory of irrational flow of fluid caused by a moving deformable body has been used to obtain the general expressions for the generalized induced mass tensors.